Leonardo da vinci - "Freud, Sigmund" (London, 2002)
This remarkable book takes as its subject one of the most outstanding men that ever lived. The ultimate prodigy, Leonardo da Vinci was an artist of great originality and power, a scientist, and a powerful thinker. According to Sigmund Freud, he was also a flawed, repressed homosexual. The first psychosexual history to be published, Leonardo da Vinci was the only biography the great psychoanalyst wrote. When Jung first saw it, he told Freud it was 'wonderful', and it remained Freud's favourite composition. The text includes the first full emergence of the concept of narcissism and develops Freud's theories of homosexuality. While based upon controversial research, the book offers a fascinating insight into two men - the subject and the author. If you've ever wondered just what lies behind the Mona Lisa's enigmatic smile, read Freud on Leonardo. It's genius on genius.
Keywords: Leonardo da Vinci-Biography